Greening development in the people Republic of China a dynamic partnership with the Asian Development Bank. (Asian Development Bank, 2021)
The green development partnership between the PRC and ADB has evolved over the years. In the report, best practices, innovations, and lessons learned from this partnership offer insights for ADB, its developing member countries, and other development partners. The report also presents forward-looking directions for further collaboration by the PRC and ADB in pursuit of a more sustainable future.